Inexpensive Synthesis of Poly(Ethylenedioxythiophene‐Sulfobetaine) Films with High Bio‐Antifouling Ability. Issue 1 (23rd January 2018) - Shen, Mo‐Yuan; Huang, Tzu‐Yang; Luo, Chun‐Hao; Huang, Yu‐Chun; Tsai, Yu‐Han; Wang, Tian‐Lin; Yu, Hsiao‐hua
Abstract : To prevent nonspecific interactions with biomolecules (e.g., proteins), blood cells, and microorganisms (e.g., bacteria, viruses, fungi, parasites) that can exert severe side effects, several bio‐inspired antifouling materials, including poly(ethylene glycol) and zwitterionic phosphocholine, sulfobetaine (SB), and carboxybetaine derivatives have been applied in biomedical electronic devices. In this paper, we report the development of an economical strategy for synthesizing ethylenedioxythiophene (EDOT)‐SB and creating the corresponding highly antifouling polymer films though electrochemical polymerization. The poly(EDOT‐SB) films inhibited 95% of the nonspecific binding of proteins from serum and prevented the adhesion of fibroblast cells. Moreover, the antifouling properties of the conducting film were maintained in both the oxidized and reduced states of PEDOT. Such zwitterionic, functionalized conducting polymer films appear to have great potential for application to bio‐electronic implant devices. Abstract : Synthesis of Poly(EDOT‐suflobetaine) film is designed for effectively avoiding non‐specific absorption of cells and proteins from serum. This bio‐interface not only provides protein‐resistive ability but also remains electrically conductive for further bio‐electronic stimulation/detection. This biocompatible film is also believed to enhance the life time of implant devices.